331. EFFECTIVENESS OF A SPECIALIZED AMINO ACID SUPPLEMENT CONTAINING CAHMB, L-ARGININE AND L-GLUTAMINE (ABOUND®) IN ESOPHAGEAL CANCER SURGERY. (24th September 2022) - Takebayashi, Katsushi; Kaida, Sachiko; Yamaguchi, Tsuyoshi; Otake, Reiko; Miyake, Toru; Kojima, Masatsugu; Maehira, Hiromitsu; Iida, Hiroya; Tani, Masaji
Abstract: The wound healing effect of the specialized amino acid supplement containing CaHMB, L-arginine and L-glutamine (Abound®) has been reported. In this study, we evaluated the effectiveness of Abound® in patients with thoracic esophageal cancer in the perioperative period. One hundred twenty-one patients who underwent esophagectomy for thoracic esophageal cancer between January 2013 and September 2021 were included. Among the 103 male and 18 female patients (median age 70 years, range 38-84 years) stage I disease was found in 41 patients, stage II in 17, stage III in 56, and stage IVa in 7. Postoperative infectious complications were evaluated between those patients who received Abound® for 7 days before surgery (n = 78) and those who did not (controls, n = 43). The baseline characteristics between two groups were balanced. The postoperative infectious complications were follows: Anastomotic leakage occurred in 5 and 8 patients (6.4% vs 18.6%; p = 0.038) pneumonia occurred in 15 and 15 patients (19.2% vs 34.8%; p = 0.056), and wound infection occurred in 1 and 3 patients (1.2% vs 6.9%; p = 0.09) in the Abound® and control groups, respectively. The rate of anastomotic leakage was significantly lower in the Abound® group than that of control group. In anastomotic leakage cases, the treatment period was shorter in the Abound® group than that of control group: 18 (7-25) vs 25 (21-56) days; p = 0.033). Abound® has the potential to reduce the incidence of infectious complications and shorten the treatment period for anastomotic leakage. Abound® may improve outcome following esophageal cancer surgery.